Poverty, food security, and the environment - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (International Food Policy Research Institute, 1995)
The condition of the world's natural resource base in the year 2020 largely depends on whether poverty has been eradicated. Poverty and environmental degradation are closely linked, often in a self-perpetuating negative spiral in which poverty accelerates environmental degradation and degradation results in or exacerbates poverty. While poverty is not the only cause of environmental degradation, it does pose the most serious environmental threat in low-income developing countries. The many millions of people who live near the subsistence minimum will exploit natural resources to survive. We must not blame the victims but must seek to eradicate extreme poverty. Accelerated agricultural intensification is a key component of the strategy to alleviate poverty and protect the environment. Sustainability of future agricultural development must be ensured, otherwise we undermine the welfare and survival of our own species. Contrary to what some will have us believe, agricultural development is part of the solution to protect the environment, not part of the problem.